Effect of different hormonal protocols with timed AI on clinical signs of estrus and conception rates in Bulgarian Murrah buffaloes - Radena Nenova (Revista Científica)
The objective of the field experiment was to study the effect of different protocols for estrus synchronization with timed artificial insemination (TAI) on the manifestation of clini- cal signs of estrus (CSE) and conception rates in the Bulgarian Murrah breed. For treatment 75 heifers and 133 buffalo cows were assigned with follicles >8 mm and no corpus luteum and subjected to the following protocols: Presynch/Ovsynch (D1 - Synchrostim + Enzaprost; D4 - Оvarelin; D11 - Enzaprost; D13 - Оvarelin), Ovsynch (D1 - Оvarelin; D8 - Enzaprost; D10 - Оva- relin), Ovsynch+PRID (D1-8 PRID DELTA; D8 - Enzaprost; D10 - Оvarelin). For the buffalo cows, each protocol was applied in the breeding and non-breeding season, while in the heifers, out of season only. Gestation was diagnosed sonographically on day 45 post-TAI. The data were processed via dispersion anal- ysis of a non-orthogonal set of qualitative traits, including the following factors with respective classes: protocol, three class- es – as described above; CSE, three classes – without CSE; patency of the cervical canal (excluding mucus); presence of clear mucous discharge (including patency); age, two classes – heifers, cows. Another 3-factor analysis was conducted on buffalo cows only, instead of age including season – with two classes: in season and out of season. The results show that the factor protocol has the most pronounced effect on TAI success (p<0.01), significantly lowest being the pregnancy rate (pi val- ues) under the Presynch/Ovsynch protocol – only 23.9%, com- pared to 40.7 and 47.4% under Ovsynch and Ovsynch+PRID, respectively. Although the effect of age is non-significant, in the heifers, Ovsynch+PRID and Ovsynch show markedly higher results (50.0 and 52.9%, respectively). At the same time, in the buffalo cows, the differences are lower, the Ovsynch pro- tocol having a relatively low pregnancy rate (38.3%), Ovsyn- ch+PRID – highest (45.0%), and Presynch/Ovsynch – lowest (30.4%). The season had no significant effect, but it is note- worthy that there are even higher conception rates after out-of- season TAI than in-season – a very well-expressed difference under Ovsynch+PRID (50.0% vs. 37.5%) and smaller under Presynch/Ovsynch (37.5% vs 28.9%) and Ovsynch (40.9% vs 36.0%). CSE is a significant source of variance of conception rates (p<0.05), predictably the highest pi value belonging to the cases with mucus. The superiority of the Ovsynch+PRID protocol finds expression in the highest incidence of full estrus (with both CSE) in the lactating buffaloes (70%) and even more in the heifers (82%), as compared to Presynch/Ovsynch (56.5 and 52.2% respectively) and Ovsynch (51.1 and 50.0%) pro- tocols. This is a reason to conclude that the Ovsynch+PRID protocol is recommendable for application in both age groups of Bulgarian Murrah buffaloes, as the observed highest mani- festation of full estrus is associated with the highest conception rates, for which mucous discharge can be used as an indicator; this to greater extent regards the heifers in which, on the other hand, the Ovsynch protocol also has high success of TAI. The tested protocols show the capacity to mitigate the impact of season on reproduction and can be used in practice for over- coming the species-problematic seasonal anestrus, especially Ovsynch+PRID.